KURIKULUM IBNU SINA DALAM PEMBENTUKAN KARAKTER DAN RELEVANSINYA DENGAN KURIKULUM MERDEKA - Lestari, Titis Wahyu Muji; Khudin, Ilham Soleh; Saidah, Nur (Al’ulum Jurnal Pendidikan Islam, 2025)
This research aims to uncover moral education in the Ibnu Sina curriculum, the Merdeka curriculum, and how the relevance of character education is within both curricula. The method used qualitative, employing a library research approach with data analysis techniques involving data summarization, presentation, drawing conclusions, or verification. The research findings indicate that the Ibnu Sina Curriculum and the Merdeka Curriculum have relevance to character education. Ibnu Sina emphasizes education through daily activities, focusing on morals, virtues, hygiene, and Islamic morals for ages 3-14. Meanwhile, in the Merdeka curriculum, character development for learners includes maximizing the functions of subjects that are enriched with character education materials (morals or values) such as Religious Education and Civic Education.Character education, morals, and ethics in the Merdeka curriculum are realized through the Pancasila student profile. The Pancasila student profile itself adheres to values of faith, piety towards God Almighty, noble morals, global diversity, mutual cooperation, independence, critical thinking, and creativity.